Gender differences in landing mechanics after anterior cruciate ligament reconstruction - Alanazi, A.; Al-Enezi, F.; Aldaihan, M.; Amer, H. A.; Ortiz, A. (British Journal of Sports Medicine, 2021)
Background: Studies have reported that females and males exhibit different landing techniques. However, few studies have examined the effect of gender on landing technique in athletes following ACLR. Objective: To compare landing technique between females and males following ACLR during landing from heading-jump (LHJ) and landing from long-jump (LLJ). Design: Cross-sectional study. Setting: Biomechanical laboratory. Patients (or Participants): Eight female and 8 male recreational athletes. Interventions (or Assessment of Risk Factors): LHJ included jumping forward to head a soccer ball and landing on the force plates, whereas LLJ included jumping forward and landing on the force plates. Main Outcome Measurements: A 2×2 ANOVA (gender × landing) was performed to evaluate kinematics, kinetics, and electromyography data. Results: A significant interaction was found only for knee flexion angles (F1,14= 12.67, p = 0.003). Pairwise comparisons showed that males landed with decreased knee flexion compared with females during LLJ (p = 0.01). LHJ showed decreased knee flexion compared with LLJ in females (p < 0.001) and males (p = 0.001). Significant main effects of landing were found. LHJ showed decreased hip flexion angles (F1,14= 71.07, p < 0.001), decreased knee flexion angles (F1,14= 95.17, p < 0.001), decreased knee extension moments (F1,14= 20.12, p = 0.001), and decreased plantarflexion moments (F1,14= 34.71, p < 0.001). Also, a significant main effect of gender for hip flexion was found showing that males landed with decreased hip flexion angles (F1,14= 7.17, p = 0.01). Conclusions: LHJ showed greater injury predisposing factors compared with LLJ. Females and males following ACLR showed nearly similar landing biomechanics. However, males landed with smaller hip and knee flexion angles (stiff-landing); therefore, preventative training programs may focus on improving the use of hip and knee joints (soft-landing) during landing to decrease the risk of consequent injuries in males following ACLR.